Peran Emas sebagai Safe Haven di Tengah Melemahnya Rupiah dan Turunnya Daya Beli Masyarakat - Abdul Halim; Dicky Perwira Ompusunggu; Tiur Rosida Simbolon (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2026)
Global economic instability triggered by the pandemic, geopolitical tensions, and tight monetary policies in developed countries have had a real impact on the weakening of the rupiah exchange rate and a decline in the purchasing power of the Indonesian people. In such conditions, gold is often regarded as a safe-haven asset capable of preserving wealth, particularly during periods of heightened economic uncertainty. This study aims to empirically analyse the role of gold as a safe haven amid the weakening of the rupiah exchange rate and the decline in consumer purchasing power. This study employs a quantitative approach using multiple linear regression. The secondary data used covers the period from January 2022 to April 2025, encompassing five variables: gold price (PG), rupiah exchange rate (KURS), inflation (INF), consumer price index (CPI), and real wages (RW). The data were analysed using EViews 13 software, through descriptive statistical tests, ADF stationarity tests, classical assumption tests, and t and F tests. The results indicate that the rupiah exchange rate has a positive and significant effect on gold prices, while inflation has a negative and significant effect. CPI and real wages do not have a significant effect on gold prices. The regression model has a coefficient of determination (R²) of 81.25%, indicating that most of the variation in gold prices can be explained by the independent variables. These findings confirm the role of gold as a hedge against rupiah depreciation, although not all purchasing power factors have a significant impact.